Effect of Theraplay-Based Play Therapy on Separation Anxiety in Elementary School Girls: A Randomized Controlled Trial - Rozita Kaviani; Nafiseh Hekmatipur (مجله دانشگاه علوم پزشکی گرگان)
Background and Objective: School-age children often experience separation anxiety due to being away from their families. A therapeutic approach to address this issue is Theraplay-based play therapy. This study aimed to determine the effectiveness of Theraplay-based play therapy on separation anxiety in elementary school girls. Methods: This randomized controlled trial involved 60 elementary school girls from Aliabad-e-Katoul County, Iran, divided into two groups of 30: A control group (mean age: 8.69±0.71 years) and an intervention group (mean age: 8.9±0.85 years) in 2023. Hahn et al.’s Separation Anxiety Assessment Scale (SAAS) (parental version, 2003) was administered as a pre-test and post-test to assess separation anxiety. The control group received no intervention. The intervention group participated in ten 45-minute Theraplay-based play therapy sessions with their mothers for 10 days. Results: The mean total separation anxiety score in the pre-test was 82.2±9.27 in the intervention group and 83.53±8.8 in the control group, showing no statistically significant differences. Similarly, there were no significant differences between the two groups in pre-test scores for separation anxiety dimensions. However, the mean total separation anxiety score in the post-test was 78.36±7.87 in the intervention group and 84.03±9.01 in the control group. This difference was statistically significant (P<0.05). Furthermore, significant differences were observed in all dimensions of separation anxiety (P<0.05) except for the frequency of events in the intervention group before and after the intervention. Conclusion: The results of this study indicate that the Theraply-based play therapy effectively reduces separation anxiety in elementary school girls.